First record of Hormiini Förster, 1863, and Macrocentrinae Förster, 1863 (Hymenoptera: Braconidae) for the fauna of Egypt, with the description of a new species - Edmardash, Yusuf A.; El-Ghiet, Usama M. Abu; Gadallah, Neveen S. (Zootaxa, 2020)
The tribe Hormiini Förster, 1863, and subfamily Macrocentrinae Förster, 1863 (Hymenoptera: Braconidae) are recorded for the first time for the Egyptian fauna. Hormiini is represented by five species in two genera, Avga Nixon, 1940, with a single new species, A. sinaitica Edmardash & Gadallah; and Hormius Nees, 1819  (4 species), H. moniliatus (Nees, 1811), H. propodealis (Belokobylskij, 1989), H. sculpturatus Tobias, 1967, and H. similis Szépligeti, 1896. One species of Macrocentrinae, Macrocentrus collaris (Spinola, 1808) is also reported here. The specimens were collected from different localities of Egypt.